Characterizing the Structural Evolution of Cereal Trade Networks in the Belt and Road Regions: A Network Analysis Approach - Wei Chen; Haipeng Zhang (Foods, 2022)
Cereal trade is essential for economic and commercial cooperation among countries along the “Belt and Road” (BRI). It helps ensure food security and contributes to building a community of interests and destinies for the BRI countries. Based on the UN Comtrade database, this study, using a network analysis approach, investigates the structural characteristics and spatiotemporal dynamics of cereal trade networks among the “Belt and Road” countries. Results show that: (1) The cereal trade among the BRI countries has formed well-connected and complex trade networks, and the “Belt and Road” initiative has significantly promoted cereal trade networks among the BRI countries. (2) The backbone structures of cereal trade networks along the BRI are in geographical proximity. India, Russia, and Ukraine are the most important trading partners and absolute core nodes in the trade networks, influencing the entire cereal trade networks. (3) The BRI cereal trade networks exhibit significant core-periphery structures, with considerable power asymmetries between the countries reflecting food supply and demand differences. In general, the BRI cereal trade networks have developed from relatively diversified to polarized. Supply chains in the cereal trade network are dominated by a few large countries and are fragile, with weak resilience and low resistance to risk. Therefore, governments should continue to strengthen regional cooperation, optimize cereal trade network structure, enhance their reserve capacity, and build a stronger system to guarantee food security and prevent risk. All these measures will support the food security of the “Belt and Road” countries.